Streptococcal Lancefield polysaccharides are critical cell wall determinants for human Group IIA secreted phospholipase A2 to exert its bactericidal effects - Hensbergen, Vincent P. van; Movert, Elin; Maat, Vincent de; Lüchtenborg, Christian; Breton, Yoann Le; Lambeau, Gérard; Payré, Christine; Henningham, Anna; Nizet, Victor; Strijp, Jos A. G. van; Brügger, Britta; Carlsson, Fredric; et al. (PLoS pathogens, 2018)
Human Group IIA secreted phospholipase A2 (hGIIA) is an acute phase protein with bactericidal activity against Gram-positive bacteria. Infection models in hGIIA transgenic mice have suggested the importance of hGIIA as an innate defense mechanism against the human pathogens Group A Streptococcus (GAS) and Group B Streptococcus (GBS). Compared to other Gram-positive bacteria, GAS is remarkably resistant to hGIIA activity. To identify GAS resistance mechanisms, we exposed a highly saturated GAS M1 transposon library to recombinant hGIIA and compared relative mutant abundance with library input through transposon-sequencing (Tn-seq). Based on transposon prevalence in the output library, we identified nine genes, including dltA and lytR, conferring increased hGIIA susceptibility. In addition, seven genes conferred increased hGIIA resistance, which included two genes, gacH and gacI that are located within the Group A Carbohydrate (GAC) gene cluster. Using GAS 5448 wild-type and the isogenic gacI mutant and gacI-complemented strains, we demonstrate that loss of the GAC N-acetylglucosamine (GlcNAc) side chain in the ΔgacI mutant increases hGIIA resistance approximately 10-fold, a phenotype that is conserved across different GAS serotypes. Increased resistance is associated with delayed penetration of hGIIA through the cell wall. Correspondingly, loss of the Lancefield Group B Carbohydrate (GBC) rendered GBS significantly more resistant to hGIIA-mediated killing. This suggests that the streptococcal Lancefield antigens, which are critical determinants for streptococcal physiology and virulence, are required for the bactericidal enzyme hGIIA to exert its bactericidal function.
Gesehen am 18.03.2020
Im Titel ist "2" nach "A" tiefgestellt